PRELIMINARY STUDY ON RECYCLING PLUTONIUM AND MINOR ACTINIDES IN PRESSURIZED WATER REACTOR (PWR) WITH THORIUM AS FUEL USING THE PIJ CELL CALCULATION MODULE OF SRAC CODE - MULYANA , DANI
The nuclear waste and the nuclear non-proliferation is part of the main issues in the development of nuclear reactor. One of the strategies offered is not to separate the plutonium and minor actinide in the reprocessing. In this study, we simulate the use of plutonium and minor actinide on Pressurized Water Reactor or PWR. With the main fuel is used thorium. For further analysis, we varied the concentration of U-233, plutonium, and minor actinide. In order to obtain more comprehensive evaluation, a comparative study on the moderator to fuel volume ratio (MFR) is also performed. In this study, the value of MFR is varied from 0.2 to 4.0. Evaluation has been also performed composition of the fuel after the burnup and neutrons spectrum in the reactor . Tthe results show that the composition of the fuel after the burnup decrease and neutrons spectrum shifted toward the higher energy region. This simulation did by using the SRAC program and utilizes nuclear data library the JENDL-3.2.